Identification of Social Problems of Farmers Using Fuzzy Mathematics - K. Revathi, G.; Amudhambigai, B.; Narmadha, V.; Poornima, T. (International Journal of Engineering and Technology, 2018)
In this article the reasons behind farmers suicide in Cauvery Delta Zone in Tamil Nadu a state in India were collected and analyzed through fuzzy sets and fuzzy logic. A fuzzy model was developed to identify the factor which causes the excessive stress on farmers to commit suicide. Finally some valuable suggestions towards the welfare of farmers also provided.Â